Stitching Together East and West: A Tale of Two Professors - Maureen P. Hall; Mary Keator (Dr. Chinmay Pandya, 2019)
There is a saying, "There is nothing new under the sun." While that may be true, what is also true is that there is a newness in combining approaches that already exist into something dynamic and extraordinary. Our work with lectio divina evidences this dynamism. We take the monastic contemplative practice of lectio divina from the West and stitch it together with the Eastern emphasis on learning as a process of character development and transformation that originates in Eastern traditions. Both lectio divina and the Eastern practices that originated in India in the yogic schools emphasize the formation of the whole person (body, mind, heart and soul). Just as yoga is the union of body and mind, lectio divina is a part of contemplative practices and pedagogy that knits together mind, body, heart in the learning process and out of this combination, something new is born into the spaces of teaching and learning. This article chronicles the conscious effort to create community between two like-minded professors who were dharmically brought together. In community with each other, they began to realize the value of stitching together Eastern and Western approaches for deepened learning and self-discovery for teachers and students alike.